A Learning Model Integrating Ethnoscience, Discovery Learning, and Digital Media for Elementary Science Education - Fita Nelyza; Ruslaini Ruslaini; Cut Maulina; Agus Kistian; Eva Novita; Abdul Gani (Jurnal Pendidikan Sains Indonesia, 2026)
Science literacy among elementary school students remains relatively low, particularly due to the lack of integration between scientific concepts, cultural context, and digital learning environments. This study aims to develop and validate an integrated learning model that combines ethnoscience, discovery learning, and digital media to support science literacy in elementary education. The study employed a design-based research approach involving literature analysis, model development, expert validation, and a limited try-out. The results indicate that the proposed model is categorized as very valid, with an average validation score of 4.4 (88%) in terms of content relevance, construct coherence, and practicality. The limited try-out results show that approximately 90% of students were actively engaged in learning activities, while 85% were able to follow the learning syntax effectively. The integration of ethnoscience provides contextual learning experiences, discovery learning facilitates active knowledge construction, and digital media enhances interactivity and conceptual understanding. Therefore, the proposed model offers a comprehensive and applicable instructional framework to support science literacy in elementary education. This study contributes to the development of integrated learning models by providing a structured and empirically supported framework that can be implemented in elementary science classrooms